QSM-IDM – A novel quadrature spatial modulation based on interleaving division multiplexing for multiple antenna system - Sherif K. El Dyasti; Esam A.A. Hagras; Hadia El-Hennawy (Digital Communications and Networks, 2019)
Quadrature Spatial Modulation (QSM) is a high spectral efficiency Multiple-Input Multiple Output (MIMO) technique used to improve the spectral efficiency of wireless communication systems. The main concept of QSM is to extend the spatial constellation of the conventional Spatial Modulation (SM) in both the in-phase and quadrature components of the data symbol. In this paper, because QSM-based on Interleaving Division Multiplexing (IDM) has not been introduced in the literature as a multiple antenna system, we introduced a novel scheme, called QSM system based on Interleaving Division Multiplexing (QSM-IDM). The antenna sets are also applied to a spreader, before being used to assign an antenna number for information transmission. Analysis and simulations for a flat fading channel show that the proposed QSM-IDM method significantly outperforms the original QSM system with the same data rate, while maintaining a relatively acceptable complexity. The obtained simulation results show that the conducted analysis yields significant improvements for the accuracy of the proposed scheme, with satisfactory complexity. Keywords: Interleaver Division Multiplexing (IDM), Multiple Input Multiple Output (MIMO), Spatial Modulation (SM), Quadrature Spatial Modulation (QSM)